Farmers' Motivation in Implementing Jajar Legowo Planting System in Tegalsari, Kepanjen, Malang - Hamyana; Khoirunisak; Ugik Romadi (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2022)
This study aims at determining the factors affecting the farmers' motivation in implementing Jajar Legowo planting system. This study was conducted in Tegalsari, Kepanjen, Malang, from April to June, 2020. The population in this study was the members of farmer groups "Baru Muncul 1" and "Baru Muncul 2" totaling 152 people. Sampling technique employed was proportionate random sampling. The number of samples was determined by adopting Slovin formula at a degree of error of 10% as many as 60 respondents. Moreover, the data in this study were collected by employing a questionnaire.  The method used for data analysis was multiple linear regression test with IBM SPSS 22 software. The results showed that internal factors (age, land area, education, length of farming) and external factors (availability of capital, intensity of extension, and availability of labor) affected farmers' motivation in implementing Jajar Legowo planting system by 65.6%, while the remaining 34.4% is affected by other variables which were unexamined in this study. The factors significantly affecting farmers' motivation in implementing Jajar Legowo planting system are internal factors (age, land area, education, length of stay), the availability of capital, the intensity of counseling, and the availability of labor.